2013
DOI: 10.1002/pola.26901
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric microstructures and dielectric properties of polynorbornenes with 3,5-bis(trifluoromethyl)biphenyl side groups by ring-opening metathesis polymerization

Abstract: exo‐Polynorbornenes containing bis(trifluoromethyl)biphenyl side groups were synthesized by ring‐opening metathesis polymerization using different Grubbs' catalysts, the microstructures of the polymer chains were established using NMR and IR spectroscopy. The influence of monomer and catalyst structures on chain microstructure was revealed and the correlation of properties with microstructure was investigated in detail. The exo‐poly(N‐3,5‐bis(trifluoromethyl)biphenyl‐norbornene‐pyrrolidine) (exo‐PTNP) and exo‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 71 publications
0
18
0
Order By: Relevance
“…Besides, the 13 C NMR spectra (Fig. 3c, d) of block copolymers showed that the signals of methylene carbon (C c ) were observed as only one single peak at 34.5–34.0 ppm, suggesting that the backbone had high stereoregularity mostly because the size of endo -N-arylpyrrolidine NBE moiety in BNP and TNP matched well with the space requirement to control the stereoselectivity of single- and double-stranded PNBE chains during ROMP process 3033,38,39 .
Fig. 3The NMR spectra of linear and monocyclic polymers.
…”
Section: Resultsmentioning
confidence: 76%
“…Besides, the 13 C NMR spectra (Fig. 3c, d) of block copolymers showed that the signals of methylene carbon (C c ) were observed as only one single peak at 34.5–34.0 ppm, suggesting that the backbone had high stereoregularity mostly because the size of endo -N-arylpyrrolidine NBE moiety in BNP and TNP matched well with the space requirement to control the stereoselectivity of single- and double-stranded PNBE chains during ROMP process 3033,38,39 .
Fig. 3The NMR spectra of linear and monocyclic polymers.
…”
Section: Resultsmentioning
confidence: 76%
“…19 To improve the processing property, conductivity and hydrophilicity of the aPNB, a simple but useful measure taken was to design and prepare polynorbornene-based hybrid membranes with exible backbones or polar functional groups. ROMP-type polynorbornene (rPNB) 20 could be prepared with a high molecular weight at normal temperatures and pressures and exhibited excellent processability. In addition, a cross-linked AEM was developed by Coates and co-workers, who employed ringopening metathesis polymerization (ROMP) of a tetraalkylammonium-functionalized norbornene with dicyclopentadiene (DCPD).…”
Section: Introductionmentioning
confidence: 99%
“…With the monomers in hand, polymers with different backbones were readily prepared for comparing their self-assembly and TAD modification characteristics (Scheme ), which were then modified by 4-(3-trifluoro­methylphenyl)-1,2,4-triazoline-3,5-dione (FTAD) (Figure S4). The third-generation Grubbs catalyst (Ru-III)-initiated ROMP of norbornene pyrrolidine derivatives and MCP of 1,6-heptadiyne derivatives can produce trans isotactic PNBE ,, and PA with five-membered rings, , respectively. Initially, MCP of SHD was performed by Ru-III at 30 °C in THF.…”
Section: Resultsmentioning
confidence: 99%